GENERATIVE PHONOLOGY: SOME FUNDAMENTAL THEORETICAL CONSIDERATIONS (Journal of Foreign Language Studies, 2020)
This article has been designed as a succinct review of some of the basic theoretical considerations in generative phonology with illustrations from English-based data. These issues are:• Generative grammar and Generative phonology;• Brief definitions of these concepts: linguistic competence vs. linguistic performance, deep structure vs. surface structure, derivational analysis;• The distinction between phonetic and phonological features in generative phonology.
Keywords: generative phonology; linguistic competence; linguistic performance; deep structure; surface structure